Policy document detailing the use of the stepwise investment approach for Climate-Smart Cocoa adoption by farmers and companies - Dalaa, Mustapha Alasan; Saeed, Abdul Razak; Kofituo, Rich Kofi; Asare, Richard (2020)
"The International Institute of Tropical Agriculture (IITA) and Rainforest Alliance (RA), in conjunction with its partners The International Center for Tropical Agriculture (CIAT), The Sustainable Food Lab (SFL) and Root Capital (RC) through the Climate Change Agriculture and Food Security’s (CCAFS) Phase 1 (2015-2018) on Mainstreaming Climate Smart Cocoa (CSC) project laid the foundation for this second phase of CCAFS. Under phase one, a lot of progress was made which led to the development of the climate exposure maps for Ghana’s cocoa sector and the recommendation of site-specific Climate smart Agriculture practices for the cocoa sector which recently being used by the Ghana COCOBOD as basis for the development of a climate smart cocoa standard. This novel approach to climate resilience, mitigation and adaptation in the cocoa sector promises to be the anchor towards sustainable production of the crop and the results of which can serve as a model for other crops in the region and beyond. What is lacking is the industries inability to push for the institutionalisation of these CSA packages (WCF Climate Smart cocoa Manual) in the training programs of companies and other certification bodies. There is also very limited data on the stepwise approach for climate smart cocoa and the need to establish a business case for CSA investment in both the cope and adjust zones. This document serves as a policy guide to help companies and cocoa sector stakeholders to adopt the use of the proposed stepwise Investment pathway using climate smart cocoa practices.